A simple polynomial-time approximation algorithm for the total variation distance between two product distributions - Feng, Weiming; Guo, Heng; Jerrum, Mark; Wang, Jiaheng (arXiv.org, 2023)
We give a simple polynomial-time approximation algorithm for the total variation distance between two product distributions.